G6PD protects from oxidative damage and improves healthspan in mice - Sandrina Nóbrega-Pereira (Nature Portfolio, 2016)
The enzyme G6PD generates the reductive metabolite NADPH, which has antioxidant effects, but has also been linked to tumour growth. Here the authors generate mice that modestly overexpress G6PD and report increased lifespan in females, and no negative effects on tumour formation in various genetic models.